Use of Moringa Oleifera Seeds as Coagulant for Groundwater Treatment in Batch Scale Study - Hashim, Nor Haslina; Santharan, Hema Rathi; Awang, Zarizi; Mohd. Arish@Arshad, Nur Aini (Penerbit UTHM, 2020)
Water is the most valuable resource and the most passionately contested which is necessary for all life on the earth. A full 71% of the Earth’s surface is covered with water and most mammals, like humans, are made up of 55-75% water [1]. Groundwater is the water that fills cracks and other openings in the bed of rocks and sand where each drop of rain that soaks into the soil moves downward to the water table, which is the water level in the groundwater reservoir. The population growth of Malaysia in 2010 is approximately 28.6 million, whereby year 2040 the population is estimated to increase until 38.6 million. The estimated water uses in Malaysia in year 2010 about 13,200 Million Liters per Day (MLD). However, by year 2020 the estimated water use will be increased to 16, 000 MLD. Besides that, the estimated groundwater use of Malaysia is 450 MLD which is approximately 3.4% of total water use, 60% for domestic, 35% for industry and 5% for the agriculture [2].